High Polymer Molecular Weight Yields Solar Cells with Simultaneously Improved Performance and Thermal Stability - Riera‐Galindo, Sergi; Sanz‐Lleó, Marta; Gutiérrez‐Fernández, Edgar; Ramos, Nicolás; Mas‐Torrent, Marta; Martín, Jaime; López‐Mir, Laura; Campoy‐Quiles, Mariano (Small (Weinheim an der Bergstrasse, Germany), 2024)
Simple synthetic routes, high active layer thickness tolerance as well as stable organic solar cells are relentlessly pursued as key enabling traits for the upscaling of organic photovoltaics. Here, the potential to address these issues by tuning donor polymer molecular weight is investigated. Specifically, the focus is on PTQ10, a polymer with low synthetic complexity, with number average molecular weights of 2.4, 6.2, 16.8, 52.9, and 54.4 kDa, in combination with three different non‐fullerene acceptors, namely Y6, Y12, and IDIC. Molecular weight, indeed, unlocks a threefold increase in power conversion efficiency for these blends. Importantly, efficiencies above 10% for blade coated devices with thicknesses between 200 and 350 nm for blends incorporating high molecular weight donor are shown. Spectroscopic, GIWAXS and charge carrier mobility data suggest that the strong photocurrent improvement with molecular weight is related to both, improved electronic transport and polymer contribution to exciton generation. Moreover, it is demonstrated that solar cells based on high molecular weight PTQ10 are more thermally stable due to a higher glass transition temperature, thus also improving device stability. This work shows how increasing the molecular weight of a low synthetic complexity polymer, PTQ10, when paired with different acceptors yielded a notable threefold enhancement in power conversion efficiency. These high‐efficiency blends show good thickness tolerance, and exhibited both improved stability and efficiency, underscoring the potential of cost‐effective organic solar cells.